Relationship Between Time in Therapeutic Range and Comparative Treatment Effect of Rivaroxaban and Warfarin: Results From the ROCKET AF Trial - Piccini, Jonathan P. (Blackwell Publishing Ltd, 2014)
BACKGROUND: Time in therapeutic range (TTR) is a standard quality measure of the use of warfarin. We assessed the relative effects of rivaroxaban versus warfarin at the level of trial center TTR (cTTR) since such analysis preserves randomized comparisons. METHODS AND RESULTS: TTR was calculated using the Rosendaal method, without exclusion of international normalized ratio (INR) values performed during warfarin initiation. Measurements during warfarin interruptions >7 days were excluded. INRs were performed via standardized finger‐stick point‐of‐care devices at least every 4 weeks. The primary efficacy endpoint (stroke or non‐central nervous system embolism) was examined by quartiles of cTTR and by cTTR as a continuous function. Centers with the highest cTTRs by quartile had lower‐risk patients as reflected by lower CHADS(2) scores (P<0.0001) and a lower prevalence of prior stroke or transient ischemic attack (P<0.0001). Sites with higher cTTR were predominantly from North America and Western Europe. The treatment effect of rivaroxaban versus warfarin on the primary endpoint was consistent across a wide range of cTTRs (P value for interaction=0.71). The hazard of major and non‐major clinically relevant bleeding increased with cTTR (P for interaction=0.001), however, the estimated reduction by rivaroxaban compared with warfarin in the hazard of intracranial hemorrhage was preserved across a wide range of threshold cTTR values. CONCLUSIONS: The treatment effect of rivaroxaban compared with warfarin for the prevention of stroke and systemic embolism is consistent regardless of cTTR.